Analysis of Income and Consumption Effects of the Reform of Pension Integration System in Zhejiang Province - Jiawei Ma, Sujuan Tong (Forest Chemicals Review, 2021)
A high-quality social security system is an institutional guarantee for achieving common prosperity. The reform of pensions in government agencies and institutions is an important reform measure to achieve common prosperity in the field of social security. This paper uses the "Decision on the Reform of the Pension Insurance System for Staff in Institutions and Institutions" as a quasi-natural experimental scenario to construct a double difference model to investigate the impact of Zhejiang’s pension insurance reform on income redistribution. The research finding shows that the dual-track "combination" reform adopts "incremental reform" and has achieved certain results, but it has not solved the original system dilemma, the gap in pension benefits is not significantly narrowed, and the income redistribution effect is not obvious.